Impacts of varying agricultural intensification on crop yield and groundwater resources: comparison of the North China Plain and US High Plains. (20th April 2015) - Pei, Hongwei; Scanlon, Bridget R; Shen, Yanjun; Reedy, Robert C; Long, Di; Liu, Changming
Abstract: Agricultural intensification is often considered the primary approach to meet rising food demand. Here we compare impacts of intensive cultivation on crop yield in the North China Plain (NCP) with less intensive cultivation in the US High Plains (USHP) and associated effects on water resources using spatial datasets. Average crop yield during the past decade from intensive double cropping of wheat and corn in the NCP was only 15% higher than the yield from less intensive single cropping of corn in the USHP, although nitrogen fertilizer application and percent of cropland that was irrigated were both ∼2 times greater in the NCP than in the USHP. Irrigation and fertilization in both regions have depleted groundwater storage and resulted in widespread groundwater nitrate contamination. The limited response to intensive management in the NCP is attributed in part to the two month shorter growing season for corn to accommodate winter wheat than that for corn in the USHP. Previous field and modeling studies of crop yield in the NCP highlight over application of N and water resulting in low nitrogen and water use efficiencies and indicate that cultivars, plant densities, soil fertility and other factors had a much greater impact on crop yields over the past few decades. The NCP–USHP comparison along with previous field and modeling studies underscores the need to weigh the yield returns from intensive management relative to the negative impacts on water resources. Future crop management should consider the many factors that contribute to yield along with optimal fertilization and irrigation to further increase crop yields while reducing adverse impacts on water resources.